Evaluation of how physical education lesson is taught according to working conditions of physical education teachers - Celal Taskıran; Mehmet Ilkım (Selcuk University, 2014)
The aim of this study is to evaluate how physical education lesson is taught according to working conditions of physical education teachers. For this aim, a survey form composed of 24 questions was applied on physical education teachers. Survey form was applied on 147 physical education teachers working at various schools throughout Malatya. Statistical processes were done according to answers of physical education teachers. Tables were used in order to understand results better. As a result of statistical process; influence rates of teachers    were given in percentages according to their gender. Moreover chi-square test in 0.05 level was applied in order to understand whether there is a difference between answers of teachers. It was observed that as a result of statistical comparisons there is a difference only in coaching according to significance level (p gt;0.05). It may be thought that it is the role of physical education teachers to tell the support of physical education course on cognitive, affective and social development of children to school management and parents and thereby make them comprehend and believe that it is the most important part of general education.